Harga dan Kualitas Pelayanan Dalam Mempengaruhi Keputusan Pembelian Pada Humble Coffee Majalengka - Maudina Dewi; Ihin Solihin (Journal of Innovation in Management, Accounting and Business, 2023)
Purchasing decisions are the main goals to be achieved by business people, including in the coffee shop business. Many factors can influence consumer purchasing decisions for a product including price and service quality. This study aims to determine the effect of price and service quality on purchasing decisions at a coffee shop in Majalengka. This research uses descriptive and verification methods. The approach used in this research is a quantitative approach. This research was conducted at Humble Coffee Majalengka with 99 respondents. Data collection techniques in this study using questionnaires or questionnaires. The results of this study indicate that, partially, both price and service quality has a positive effect on the purchasing decisions of Humble Coffee Majalengka consumers. Price and service quality simultaneously influence consumer decisions in buying coffee at Humble Coffee Majalengka. With these results, the conclusion of this study is that price and service quality have a positive and significant effect on purchasing decisions.